Encyclopedia of Islam and the Muslim world - Martin, Richard C. (Gale virtual reference library, 2016)
This reference work includes articles on the history, religion, cultural practices, and political economies of Muslims from the seventh-century in West Asia to today's Muslim societies throughout the continents of Asia, Africa, the Subcontinent, Europe, and the Americas.